2016
DOI: 10.1088/0741-3335/58/5/054001
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation statistics in the scrape-off layer of Alcator C-Mod

Abstract: We study long time series of the ion saturation current and floating potential, sampled by Langmuir probes dwelled in the outboard mid-plane scrape off layer and embedded in the lower divertor baffle of Alcator C-Mod. A series of ohmically heated L-mode plasma discharges is investigated with line-averaged plasma density ranging from n e /n G = 0.15 to 0.42, where n G is the Greenwald density. All ion saturation current time series that are sampled in the far scrape-off layer are characterized by large-amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(86 citation statements)
references
References 72 publications
17
69
0
Order By: Relevance
“…The ion temperature at the LCFS is assumed to be T T i e 0 0 = , since no ion temperature measurement was available for that discharge. Resistivity can affect substantially blobs dynamics by electrically disconnecting from the target sheaths and subsequently increasing their convective velocity, as predicted in [25] and experimentally measured in [4,27,28]. The influence of resistivity on blob dynamics has been investigated with seeded simulations in [17,29].…”
Section: Nonlinear Simulations With the Gbs Codementioning
confidence: 93%
“…The ion temperature at the LCFS is assumed to be T T i e 0 0 = , since no ion temperature measurement was available for that discharge. Resistivity can affect substantially blobs dynamics by electrically disconnecting from the target sheaths and subsequently increasing their convective velocity, as predicted in [25] and experimentally measured in [4,27,28]. The influence of resistivity on blob dynamics has been investigated with seeded simulations in [17,29].…”
Section: Nonlinear Simulations With the Gbs Codementioning
confidence: 93%
“…The statistical properties of these bursts in the SOL of several tokamak plasmas have recently been elucidated by the analysis of long data time series from probe measurements and gas puff imaging. [11][12][13][14][15] Conditional averaging has revealed exponentially distributed burst amplitudes and waiting times, while the burst duration is found to be constant. The wave-form for largeamplitude bursts in the time series is well described by an exponential function.…”
Section: Introductionmentioning
confidence: 97%
“…[6][7][8][9][10] The average SOL plasma density and the particle and heat fluxes due to the radial motion of plasma filaments depend on their velocity, amplitude, and frequency of occurrence. [11][12][13][14][15] The turbulence-driven transport results in broad plasma profiles in the SOL and enhanced levels of plasma--wall interactions that may be an issue for the next generation plasma confinement experiments and future fusion power reactors. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The radial motion of blob-like structures leads to largeamplitude bursts in single-point measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[78][79][80][81][82][83][84] From single-point measurements it has been demonstrated that there is an exponential distribution of both the peak amplitudes and the waiting times between them. Moreover, the average duration time does not depend on the amplitude and also appears to be robust against changes in plasma parameters.…”
Section: Introductionmentioning
confidence: 99%